A qualitative study exploring school nurses' experiences of safeguarding adolescents. (2nd May 2019) - Littler, Nadine
Abstract : Background: An integral aspect of the school nurse's role is in safeguarding; therefore, they are uniquely placed to identify and assess adolescent's health and wellbeing. Aims: The aim of this study is to explore school nurses' experiences of safeguarding adolescence. Methods: A qualitative phenomenological study was undertaken with participants recruited from five NHS trusts across England, involving semi-structured telephone interviews, which were analysed and managed with the ATLASti software using a grounded theory approach. Findings: Four categories were identified in the study, one was related to education, and three were related to the school nursing role. These include targeted interventions, encountering increased numbers of safeguarding risks (such as child sexual exploitation and mental health in practice), and identifying safeguarding supervision and teamwork as key factors of support within their role. Conclusions: This study has provided an insight into the school nurses' role in safeguarding adolescents; however, further research still needs to be undertaken on this multifaceted area of practice.